2020
DOI: 10.1177/1078155220950412
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy services in an ambulatory oncology clinic: Patient perception and satisfaction

Abstract: Introduction Studies have shown that patients rate pharmacists more favourably when the pharmacist expresses interest in the patient and attends to patients’ perspectives. There is limited available evidence evaluating both patient perception and satisfaction regarding clinical pharmacy services provided in an ambulatory oncology clinic. Methods This was a prospective mixed methods study involving surveys and patient interviews. Consenting participants completed a survey at their first visit evaluating their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The important pharmacist role in providing patient-centered chemotherapy counseling and expert medication support has been consistently demonstrated. 19 , 22 With increasing adoption of virtual healthcare for oncology patients (not requiring physical assessment), pharmacists have an opportunity to lead/develop transcendent strategies to encompass these modalities into their clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…The important pharmacist role in providing patient-centered chemotherapy counseling and expert medication support has been consistently demonstrated. 19 , 22 With increasing adoption of virtual healthcare for oncology patients (not requiring physical assessment), pharmacists have an opportunity to lead/develop transcendent strategies to encompass these modalities into their clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a study reported in Canada that patients have valued the pharmacist's initiative to meet them in the clinic, the education provided by pharmacist, and the pharmacist's accessibility throughout treatment. 39,[41][42][43] On the other hand, around 44% of patients were not satisfied with PC service. This patient dissatisfaction may be due to lack of particular clinical pharmacist assignment, history of previous admission, number of medications taken per day and length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Study conducted in Canada in 2021 on 35 patients experiencing anticancer therapy showed very high patient satisfaction with counseling services, where the average satisfaction score was 5.90-6.70 out of 7 possibilities (Munro et al 2021). Patient satisfaction is based on indicators of comfort during counseling, ease of delivery of treatment information, and good communication between patients and pharmacists (Munro et al 2021).…”
Section: Crosssectional Studymentioning
confidence: 99%
“…Study conducted in Canada in 2021 on 35 patients experiencing anticancer therapy showed very high patient satisfaction with counseling services, where the average satisfaction score was 5.90-6.70 out of 7 possibilities (Munro et al 2021). Patient satisfaction is based on indicators of comfort during counseling, ease of delivery of treatment information, and good communication between patients and pharmacists (Munro et al 2021). The pharmacist provided the majority of respondents with all of the information they required, and the interview left them extremely satisfied with their relationships with oncology pharmacists: the feeling of being supported by the pharmacist may not only improve emotional well-being but also improve the quality of care received if patients communicate with pharmacists about emerging issues and adhere to recommended pharmaceutical treatments (Munro et al 2021).…”
Section: Crosssectional Studymentioning
confidence: 99%
See 1 more Smart Citation